2014
DOI: 10.1111/jar.12117
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Training Needs for Mainstream Healthcare Professionals, to Prepare Them for Working with Individuals with Intellectual Disabilities: A Systematic Review

Abstract: This review highlights the existing themes of training needs as identified by mainstream healthcare staff. It would appear that it may be possible to produce a core training package, suitable across professions with elements that are profession specific and therefore tailored accordingly. Limitations of the literature are explored within this review, as are recommendations for the directions of future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 27 publications
3
59
0
1
Order By: Relevance
“…Qualitative data showed that all participants interviewed could identify changes to their practice that they attributed to the training sessions. The four key themes from the interviews of “increased awareness and sensitivity”, “adaptation and simplification of communication”, “adaptation and simplification of materials” and “adaptation and simplification of interventions” are consistent both with previously identified adaptations to therapy used with people with intellectual disabilities (Whitehouse, Tudway, Look, & Kroese, ) and with training needs identified for mainstream staff considering working with people with intellectual disabilities (Hemm et al., ; Werner & Stawski, ). Qualitative interviews were included in this study to give insight into the changes in “skills” introduced by the training.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Qualitative data showed that all participants interviewed could identify changes to their practice that they attributed to the training sessions. The four key themes from the interviews of “increased awareness and sensitivity”, “adaptation and simplification of communication”, “adaptation and simplification of materials” and “adaptation and simplification of interventions” are consistent both with previously identified adaptations to therapy used with people with intellectual disabilities (Whitehouse, Tudway, Look, & Kroese, ) and with training needs identified for mainstream staff considering working with people with intellectual disabilities (Hemm et al., ; Werner & Stawski, ). Qualitative interviews were included in this study to give insight into the changes in “skills” introduced by the training.…”
Section: Discussionsupporting
confidence: 79%
“…The training programmes reviewed had a wide range of duration and content. Hemm, Dagnan, and Meyer () reviewed studies of training needs for health professionals who did not primarily work with people with intellectual disabilities. They found that training needs tended to be identified in the areas of general communication, role‐specific knowledge/information and profession and role‐specific needs.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that DP report unmet needs as a result of hampered accessibility. [22][23][24][25] DP's needs are often unrecognized because of unawareness or lacking knowledge of health care professionals. [13][14][15][16] To ensure best quality of care for DP, health care professionals' needs should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…An approach similar to Smith et al can be pursued: teaching students from the point of view of service users and their experiences in trying to get access to necessary health care might be an innovative and intriguing way to educate health care professionals. [43] Moreover, a review of Hemm et al [25] shows that it is feasible to design a training package that can be deployed in different settings and consequently for different profession groups. Therefore, it would be interesting to develop multidisciplinary, on the job training to tackle common, everyday challenges that professionals, working in residential facilities, as well as PCN, are confronted with in their care for DP.…”
Section: Recommendationsmentioning
confidence: 99%
“…Whilst many barriers to accessing and receiving timely and appropriate care are highlighted in the literature, a recurring and important theme concerns communication barriers. These may relate to difficulties with communicating symptoms especially where individuals have severe or profound intellectual disabilities (Kelly et al., ), challenges related to recall, comprehension and consent (Nguyen, Lennox, & Ware, ), and healthcare staff feeling inadequately prepared to meet the communication needs of people with intellectual disabilities (Hemm, Dagnan, & Meyer, ). Such barriers can pose a threat to safety where key information cannot be communicated in a timely manner: for example where allergies or other contraindications exist, where pain behaviours are not understood or where specific support needs such as those related to dysphagia are not recognised and met.…”
Section: Introductionmentioning
confidence: 99%